Development of Learning Media Based on Video Tutorial Service Techniques in The Game of Sepak Takraw at SMP Negeri 4 Kubutambahan - Ketut Peri Ardiasa; Semarayasa, I Ketut; Suwiwa, I Gede (STKIP Paasundan Press, 2025)
This research aims to describe the design, determine the validity of results and determine the practicality of learning media based on video tutorials on service techniques in the sepak takraw game at SMP Negeri 4 Kubucepatn. This development research was carried out through 5 stages, namely analysis, design, development, implementation, evaluation. The data collection methods used were interviews and questionnaires. The results of this development research show that: video tutorial-based learning media obtained validation percentage results from content/material experts of 96%, design experts of 86%, media experts of 93%, teacher/field practitioner expert responses of 98%, student responses namely the individual test obtained a percentage result of 99%, the small group test was 97%, the large group test was 96%, so it was declared to have very good validity, and obtained an assessment from the practicality test of 97% with a very good category qualification. Good. So it can be concluded that the learning media based on video tutorials on service techniques in the sepak takraw game is declared feasible and practical to use in learning activities.